2013
DOI: 10.1002/gcc.22064
|View full text |Cite
|
Sign up to set email alerts
|

NUP98NSD1 gene fusion and its related gene expression signature are strongly associated with a poor prognosis in pediatric acute myeloid leukemia

Abstract: The cryptic t(5;11)(q35;p15.5) creates a fusion gene between the NUP98 and NSD1 genes. To ascertain the significance of this gene fusion, we explored its frequency, clinical impact, and gene expression pattern using DNA microarray in pediatric acute myeloid leukemia (AML) patients. NUP98-NSD1 fusion transcripts were detected in 6 (4.8%) of 124 pediatric AML patients. Supervised hierarchical clustering analyses using probe sets that were differentially expressed in these patients detected a characteristic gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 38 publications
(46 reference statements)
4
39
0
Order By: Relevance
“…This recurrent translocation at t(5;11)(q35;p15.5) contains the FG-repeat domain of NUP98, a nucleoporin protein family member that can interact with the histone acetyltransferase CBP/p300 and the C-terminal of NSD1 that retains the five PHD fingers, the Cys-His rich domain (C5HCH), one PWWP domain, and the catalytic SET domain. NUP98-NSD1 is the most frequent (4%–5% of cases) fusion reported in pediatric AML and is associated with poor prognosis (Shiba et al 2013). Retroviral infection of NUP98-NSD1 enhanced expression of HoxA7, HoxA7, HoxA9, and Meis1 proto-oncogenes (Wang et al 2007).…”
Section: Nsd1 Role In Cancermentioning
confidence: 99%
“…This recurrent translocation at t(5;11)(q35;p15.5) contains the FG-repeat domain of NUP98, a nucleoporin protein family member that can interact with the histone acetyltransferase CBP/p300 and the C-terminal of NSD1 that retains the five PHD fingers, the Cys-His rich domain (C5HCH), one PWWP domain, and the catalytic SET domain. NUP98-NSD1 is the most frequent (4%–5% of cases) fusion reported in pediatric AML and is associated with poor prognosis (Shiba et al 2013). Retroviral infection of NUP98-NSD1 enhanced expression of HoxA7, HoxA7, HoxA9, and Meis1 proto-oncogenes (Wang et al 2007).…”
Section: Nsd1 Role In Cancermentioning
confidence: 99%
“…NUP98 / NSD1 fusion due to the cryptic t(5;11)(q35;p15) occurs in almost 20% of children with cytogenetic normal AML (Hollink et al , ) and is often associated with FLT3 ‐internal tandem duplication (ITD) and a very poor outcome and salvage rate (Shiba et al , ). The data on HSCT in NUP98 / NSD1 are very sparse but suggest a benefit of HSCT in CR1 (Shiba et al , ).…”
Section: Indications For Hsctmentioning
confidence: 99%
“…[15][16][17][18] In recent studies analyzing the prevalence and clinical significance of NUP98/NSD1 in adult and pediatric AML patients, the investigators found that patients with NUP98/ NSD1 were more likely to also have FLT3/ITD. 11,[19][20][21][22] Despite the previous reported association between FLT3/ITD and NUP98/ NSD1, the prevalence and clinical significance of NUP98/NSD1 in FLT3/ITD AML have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%